PENDANAAN PT PNM SEBAGAI INSTRUMEN PEMBERDAYAAN EKONOMI UMKM: STUDI KASUS DI PARIT CULUM I - Desy Sutiani, Ajeng; Mustofa, M. Arif; Fatimah, Siti; Kartika Devi, Erwina; Wargo, Wargo (Fakultas Ekonomi dan Bisnis, Universitas Teknologi Sumbawa, 2025)
This study aims to examine the role of PT Permodalan Nasional Madani (PNM) in supporting the growth of Micro, Small, and Medium Enterprises (MSMEs) in Parit Culum I Subdistrict, Tanjung Jabung Timur Regency, Jambi Province. Using a descriptive qualitative approach, the study highlights the effectiveness of the PNM Mekaar group-based financing program, which targets underprivileged women. The research reveals that the unsecured funding scheme, combined with entrepreneurship training, business mentoring, and financial literacy, has been effective in enhancing the production capacity, income, and economic independence of MSME actors. Moreover, the program fosters social networks among entrepreneurs, which strengthens business resilience. Despite the positive impacts, challenges remain, such as low digital literacy, limited mentoring outreach, and minimal access to broader markets. These findings underscore the importance of integrating inclusive financing with continuous development support as part of a local economic empowerment strategy centered on MSMEs.